Potential benefits of gas mixtures to speed up rehabilitation in elite cycling sport - Bukov, Y. A.; Bukova, L. M.; Malygina, V. I.; Khodorchenko, V. M.; Safronova, P. S. (Theory and Practice of Physical Culture, 2018)
In view of particular importance of rehabilitation measures being carried out in conditions of intensification of training and competitive processes, it is extremely important to find the most effective means of rehabilitation, including using various gas mixtures which components can have a targeted effect on various mechanisms underlying the rehabilitation processes.